BIAS NILAI PENDIDIKAN DALAM KONSTRUKSI SOSIAL MASYARAKAT BIMA - Imam Yuliadi (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2017)
Education function to develop the ability and form the character and civilization of a dignified nation in order to educate the nation’s life. This is in line with the values and norms of Indonesian society is far from materialism, But along with the influx of globalization and modernization, the value and meaning of education is often biased. The occurrence of bias in the interpretation of the meaning of education is caused by social change. research of education bias in Bima community gives an idea how education values can not be interpreted well by a society. Peter L Berger is one of the sociologists who discussed the whole process of social construction. Using the social construction theory of Peter L Berger, it can be seen that the people of Bima undergo a process of social change consisting of; (a) Changes in education patterns in Bima from Islamic education to secular education, (b) Conversion of society’s high social status, related to education which is a social construction process in Bima society about one’s social status. So from the analysis can be seen that education for the community Bima has a very important role in determining the position of a person’s social status. Keywords: Value of Education, Social Construction, Society of Bima